Interaction of infectious bursal disease virus with the immune system of poultry. Issue 4 (1st December 2016) - Rehman, Z.U.; Meng, C.; Umar, S.; Munir, M.; Ding, C.
Abstract : Immune dysfunction can be either at the humoral or cellular levels and is mediated by a myriad of factors including virus-induced immunosuppression. Infectious bursal disease virus (IBDV) affects domesticated poultry and causing health problems mainly due to prolonged immunosuppression. Destruction of the immunoglobulin-producing cells is the principal cause of IBDV-induced immunosuppression, which leads to significant impairment of the primary antibody responses. Due to these effects, IBDV infection not only increases the susceptibility of poultry to other viral infections but predisposes the host to several other bacteria of variable pathologies. The IBDV-induced immune-suppression is well-known phenomenon, however, recently there have been significant advancements in understanding the molecular mechanisms of this immune-suppression. This review discuss current updates regarding the immunotoxic and immunosuppressive nature of IBDV in the poultry and highlights areas requiring future research attentions that may help to establish foundations for effective and improved vaccines against IBDV.